THE APPLICATION OF THE BUERGER ALLEN EXERCISE TO THE MANAGEMENT OF PERIPHERAL PERFUSION DISORDERS IN PATIENTS WITH TYPE II DIABETES MELLITUS IN DR. SOEDARSO HOSPITAL: CASE REPORT - Ardiansyah, Fakrul; Tias, Warentika; Suhendra, Suhendra; Baedlawi, Azhari; Amandus, Hieronimus; Handayani, Vitria Wuri (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: Diabetes Mellitus, a'silent killer', causes hyperglycemia and metabolic problems. Ineffective peripheral tissue perfusion is a nursing concern that must be treated soon to avoid problems. The test measures the Ankle Brachial Index (ABI). Medical and lifestyle-based treatments for type II diabetic mellitus (DM) exist. Purpose: The Buerger Allen Exercise (BAE) approach improves limb blood flow and is being studied in type II diabetics, Pontianak’s Dr. Soedarso Hospital Murai Room Methods: Descriptive observation is used in this case report. Typhus with Type II Diabetes Mellitus case study of 38-year-old Mrs. D. Writing data was collected through head-to-toe assessment, interviews, diagnostic exams, and BAE therapy (once daily for 3 days, ± 20 minutes). Results: Mrs. D had frequent thirst, numb feet, tingling, and a fluctuating fever. HBA1C 12.08 (H), Tubex 6 positive, P-LCR: 25.7 (H), ABI value on the first day of the right foot and hand 0.85, left 0.84. Insufficient peripheral perfusion is the main nursing diagnosis. Circulation care is provided. On the third day, the right foot and hand ABI is 0.94 and the left 0.97. Conclusion: The Buerger Allen Exercise enhances the client's lower extremity hemodynamics, which improves blood circulation in peripheral circulatory problems. Type II DM patients can avoid peripheral artery disease with BAE. BAE prevents type II diabetic peripheral artery disease.